Pendidikan Agama Kristen di Ranah Publik: Menerjemahkan Nilai Gotong Royong Kristen dalam Kerja Bakti Rukun Tetangga (Lembaga Pengembangan Kinerja Dosen, 2026)
Mutual cooperation in community service activities in the neighborhood association 010 has been going on for a long time, but Christian religious education has not yet maximally contributed to the community members, so that Christian values ​​have not been maximally internalized. This paper aims to explain the values ​​of Christian religious education internalized for community members through mutual cooperation in community service in the neighborhood association. The research method used is descriptive qualitative research with a literature study and documentation approach. The results found through the research are that the awareness of the community members of the neighborhood association 010 Empaong Muna Hamlet in mutual cooperation in community service has improved and they are continuously motivated to maintain environmental cleanliness. This research can be concluded that every community member of the neighborhood association has an awareness to maintain environmental cleanliness continuously, so that harmony, peace, and tranquility will be created in life.